Vascular bundle modifications in nodes and internodes of climbing Marantaceae. (30th October 2020) - Krähmer, Hansjörg; Hesse, Linnea; Krüger, Friederike; Speck, Thomas; Claßen-Bockhoff, Regine
Abstract: Nodes are interfaces between stems and leaves. Vascular bundles originate here and elongate into leaves and internodes. In Marantaceae, internodal bundles are highly diverse, including inverted bundles in the climbing genus Haumania . The objective of this paper is to characterize bundle forms, their position across the stem and their connection to leaves and short shoots in Haumania spp. and other unrelated African branch-angle climbers in the family ( Hypselodelphys, Trachyphrynium ). We question whether bundle inversion is a genus-specific trait in Haumania or related to the climbing growth form. Vascular bundles in internodes are scattered across the stem diameter in a characteristic pattern. Four (to five) bundle types follow each other in a centripetal order from highly sclerenchymatic 'a'-bundles close to the epidermis to 'd'-bundles in the centre with a low sclerenchyma proportion. Inverted bundles only appear in internodes of Haumania, making this trait a synapomorphy for the genus. The nodes show stem, leaf and short shoot bundles in a remarkably diverse pattern with partitioned phloem clusters and apparently augmented xylem elements. Our preliminary conclusion is that the inversion of bundles happens when leaf and short shoot traces join the main axis bundle layers.